HLA‐G gene polymorphisms associated with susceptibility to rheumatoid arthritis disease and its severity in Brazilian patients. Issue 3 (23rd June 2014) - Catamo, E.; Addobbati, C.; Segat, L.; Sotero Fragoso, T.; Domingues Barbosa, A.; Tavares Dantas, A.; de Ataíde Mariz, H.; F. da Rocha, L.; Branco Pinto Duarte, A. L.; Monasta, L.; Sandrin‐Garcia, P.; Crovella, S.
Abstract We analyzed the possible association between human leukocyte antigen‐G (HLA‐G) genetic variants, supposed to regulate HLA‐G expression, and the susceptibility to develop rheumatoid arthritis (RA) as well as its clinical manifestations. The 5′upstream regulatory region (5′URR) and 3′untranslated region (3′UTR) regions of the HLA‐G gene were screened in 127 RA patients and 128 controls: 10 5′URR and 3 3′UTR HLA‐G polymorphisms as well as two haplotypes were associated with risk for RA development, while a polymorphism in the 5′URR showed an association with the degree of disease activity. These findings, although the number of cases analyzed is limited and the P‐values are modest, indicate a possible association between HLA‐G gene polymorphisms and susceptibility to develop RA disease and its severity.